Personalized preventive medicine using genomic information: future perspective and corresponding research plan - Narimatsu, Hiroto; Watanabe, Kaname; Sato, Ann; Haneda, Eri; Okamoto, Masumi; Nakada, Haruka; Nakamura, Sho (Frontiers in Oncology, 2025)
Personalized cancer screening guided by genomic information holds the potential for effective cancer prevention. However, current approaches face challenges, including the low risk associated with most genetic variants and limited experience in genetic counseling for healthy individuals. We are initiating a feasibility study that employs a germline cancer genomic panel of 30–80 high-risk cancer genes, such as BRCA1 and BRCA2, to identify individuals with pathogenic variants. Genetic counseling will be conducted by certified medical doctors and genetic counselors utilizing the Kanagawa Prospective “ME-BYO” Cohort Study. This initiative seeks to adapt hereditary cancer counseling practices to preventive medicine, addressing the differences in counseling between clinical and preventive settings. It aims to establish a framework for personalized cancer screening, contributing to future guidelines for identifying individuals at high risk of hereditary cancers. This research will help bridge the gap between genomic research and practical preventive medicine, paving the way for personalized cancer screening strategies based on genetic information.